The Role of Tax Incentives During the Covid-19 Pandemic Period and Stable Sustainable Economic Growth - Ida I Dewa Ayu Manik SASTRI; Luh Kade DATRINI; Ni Putu PERTAMAWATI (Indonesia Strategic Sustainability, 2021)
The COVID-19 pandemic is a national disaster so the need for arrangements to support the handling of COVID-19 continues to be pursued. The real sector is expected to be able to survive and not terminate employment. The multiplier effect due to the covid pandemic requires government assistance as a policyholder. Taxes are a source of state finance, now changing to a second function, namely the regular function. Government Regulation No. 23, 44, 86, 110 and 143 regarding tax incentives for taxpayers affected by the coronavirus pandemic 19. Of the total 68,101 taxpayers at the Directorate General of Taxes in Bali, only 16,624 take advantage of tax incentives, so it must be investigated why taxpayers do not make optimal use of incentives that should be used to stimulate economic growth. The methodology used in this study is a descriptive interpretative qualitative method. The results of the study found that incentives used by taxpayers have stimulated economic growth, but there are taxpayers who do not take advantage of incentives due to the complexity of procedures and some do not receive information about incentives so that in the future the Directorate General of Taxes needs to simplify procedures and wider socialization.